Peroneal Electrical Transcutaneous NeuroModulation as a New Treatment for Patients with Overactive Bladder: An Initial Clinical Experience - Krhut, Jan; Rejchrt, Michal; Skugarevska, Barbora; Grepl, Michal; Zvara, Peter (Urologia internationalis, 2022)
INTRODUCTION: The aim of this study was to determine whether peroneal electrical Transcutaneous NeuroModulation (peroneal eTNM®) using the URIS® neuromodulation system can be used in individuals with refractory overactive bladder (OAB). METHODS: Eighteen female patients with idiopathic OAB who failed previous behavioral and pharmacological therapy were enrolled. Patients were treated with the URIS® neuromodulation system using active electrodes placed on the popliteal fossa, targeting the peroneal nerve for 30 min once a week for 12 weeks. Changes in OAB symptoms and patient-reported outcomes from baseline to the end of the study were analyzed. A nonparametric Wilcoxon signed-rank test was used to assess changes in variables. Statistical significance was defined as p ≤ 0.05. RESULTS: We observed a significant reduction in micturition frequency (p = 0.022), number of severe urgency episodes (p < 0.001), urgency incontinence episodes (p = 0.001), and nocturia episodes (p = 0.027). A decrease in Patient Perception of Bladder Condition score (p < 0.001) was also observed. Posttreatment, 15 patients (83.3%) reported a moderate or significant reduction in their bladder bother. Throughout the study, two adverse events were recorded with no causal relationship to the study treatment. DISCUSSION/CONCLUSIONS: Our study documented a significant reduction in all OAB symptoms and an improvement in all patient-reported outcomes in patients treated with peroneal eTNM® using the URIS® neuromodulation system.
Keywords: Peroneal nerve; hodnocení výsledků péče pacientem; hyperaktivní močový měchýř; Nocturia; Humans; Patient-reported outcomes; Overactive bladder; Female; výsledek terapie; lidé; Neuromodulation; inkontinence moči; nykturie; Urinary Incontinence; ženské pohlaví; Treatment Outcome; Urgency; Urinary Bladder, Overactive; Patient Reported Outcome Measures